Acetonitrile Recovery by Distillation Techniques Combined with Salting‐Out or Sugaring‐Out in Tandem. Issue 4 (16th February 2021) - Mendonça da Silva Amorim, Patrícia; Busko Di Vitta, Patricia; Converti, Attilio; Pinheiro de Souza Oliveira, Ricardo
Abstract: Acetonitrile recovery from a residual aqueous solution was performed by different techniques. Particularly, a residual acetonitrile‐water solution used in high‐performance liquid chromatography analyses at the School of Pharmaceutical Sciences of the University of São Paulo was investigated with the aim to identify the most feasible way to treat such a waste and recover acetonitrile within its dependencies. Three procedures were set up and tested, which consisted of different combinations of well‐known separation techniques, such as fractional distillation, cooling, salting‐out, and sugaring‐out. Cooling followed by distillation and subsequent addition of calcium chloride allowed to recover the highest amount of acetonitrile with a purity greater than 95 %. Abstract : The recovery of acetonitrile (ACN) from waste brings a series of advantages in terms of financial, social, and environmental aspects. ACN recovery from a residual aqueous solution was done by different combinations of fractional distillation, cooling, salting‐out, and sugaring‐out. Cooling followed by distillation and subsequent addition of calcium chloride allowed to recover the highest amount of ACN.